2001
DOI: 10.1001/archopht.119.11.1625
|View full text |Cite
|
Sign up to set email alerts
|

Cycloplegic Refractions in Healthy Children Aged 1 Through 48 Months

Abstract: Objectives: To provide a description of refractive errors in healthy, term-born children, aged 1 through 48 months, and to test the hypotheses that spherical equivalent becomes significantly less hyperopic and less variable with increasing age. Methods: Following a prospective, cross-sectional design, cycloplegic retinoscopy was used to measure the refractive error in both eyes of 514 healthy, term-born children in 12 age groups. Three hundred were aged 12 months or younger. Spherical equivalent and cylindrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
198
4
5

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(234 citation statements)
references
References 17 publications
15
198
4
5
Order By: Relevance
“…[42][43][44][45] Trichomegaly could be related to the high degree of consanguinity between the parents as suggested by Harrison and Mullaney 46 and not part of a syndrome.…”
Section: Eyementioning
confidence: 89%
“…[42][43][44][45] Trichomegaly could be related to the high degree of consanguinity between the parents as suggested by Harrison and Mullaney 46 and not part of a syndrome.…”
Section: Eyementioning
confidence: 89%
“…Em relação aos casos em que a ametropia era maior ou igual a 2,00 DC, o mesmo estudo mostrou freqüência de 5,7% em crianças até 15 meses, valor semelhante ao observado na presente amostra. Em um estudo (17) , ao fazer retinoscopia sob cicloplegia em crianças até 48 meses, os autores encontraram astigmatismo maior do que 1,00 DC em 25% das crianças e acima de 2,00 DC em 3%.…”
Section: Discussionunclassified
“…Estes achados se chocam com a maioria dos trabalhos anteriores. Em outro estudo, o autor (18) encontrou freqüência do tipo contra a regra duas vezes e meia maior do que a favor da regra em crianças cicloplegiadas abaixo de 3,5 anos, quando passou a predominar o astigmatismo a favor da regra; outros (17) encontraram astigmatismo contra a regra em 56% das crianças até 48 meses, a favor da regra em 29% e oblíquo em 14%.…”
Section: Discussionunclassified
“…[5][6][7] Epidemiological studies in Western populations have collectively shown the prevalence of myopia to be low (<5%) in children aged 8 years or younger. [8][9][10][11][12][13][14] However, studies in Asian children suggest a significantly higher prevalence of myopia, affecting 9% to 15% of preschool children 15,16 and 29% of primary school children in Singapore. 17 A study of 10,000 Taiwanese school children found that the prevalence of myopia was 6% in 6-yearolds, with the prevalence increasing to more than 70% by age of 15 years.…”
Section: Discussionmentioning
confidence: 99%